Amplitude, frequency and drivers of Caspian Sea lake‐level variations during the Early Pleistocene and their impact on a protected wave‐dominated coastline. Issue 1 (14th October 2019) - Jorissen, Elisabeth L.; Abels, Hemmo A.; Wesselingh, Frank P.; Lazarev, Sergei; Aghayeva, Vusala; Krijgsman, Wout
Abstract: The Caspian Sea, the largest isolated lake in the world, witnessed drastic lake‐level variations during the Quaternary. This restricted basin appears very sensitive to lake‐level variations, due to important variations in regional evaporation, precipitation and runoff. The amplitude, frequency and drivers of these lake‐level changes are still poorly documented and understood. Studying geological records of the Caspian Sea might be the key to better comprehend the complexity of these oscillations. The Hajigabul section documents sediment deposited on the northern margin of the Kura Basin, a former embayment of the Caspian Sea. The 2035 m thick, well‐exposed section was previously dated by magneto‐biostratigraphic techniques and provides an excellent record of Early Pleistocene environmental, lake‐level and climate changes. Within this succession, the 1050 m thick Apsheronian regional stage, between ca 2·1 Ma and 0·85 Ma, represents a particular time interval with 20 regressive sequences documented by sedimentary and palaeontological changes. Sequences are regressing from offshore to coastal, lagoonal or terrestrial settings and are bounded by abrupt flooding events. Sediment reveals a low energy, wave‐dominated, reflective beach system. Wave baselines delimiting each facies association appear to be located at shallower bathymetries compared to the open ocean. Water depth estimations of the wave baselines allow reconstruction of a lake‐level curve, recording oscillations of ca 40 m amplitude. Cyclostratigraphic analyses display lake‐level frequency close to 41 kyr, pointing to allogenic forcing, dominated by obliquity cycles and suggesting a direct or indirect link with high‐latitude climates and environments. This study provides a detailed lake‐level curve for the Early Pleistocene Caspian Sea and constitutes a first step towards a better comprehension of the magnitude, occurrence and forcing mechanisms of Caspian Sea lake‐level changes. Facies models developed in this study regarding sedimentary architectures of palaeocoastlines affected by repeated lake‐level fluctuations may form good analogues for other (semi‐)isolated basins worldwide.